LAUDATIO. PROFESSOR IOAN BÂLDEA AT HIS 80ᵀᴴ ANNIVERSARY - CSAVDÁRI, Alexandra Ana (Studia Universitatis Babeș-Bolyai Chemia, 2019)
A decade ago, Volume 54(3)/2009 of Studia Universitatis Babeș-Bolyai Chemia, was dedicated to Professor Ioan Bâldea at his 70th birthday, along with wishes of health in the many years to come as well as the spice of current valuable scientific activity. And indeed, he shared his passion as well as joy in research and study within his Alma Mater. He continued coordinating PhD students in physical chemistry, chemical technology and pharmacology. He recently rejoined teaching with inspiring liveliness, by initiating a series of plenaries that discuss either novel, sensitive or complex aspects of organic reaction mechanisms and physical chemistry (thermodynamics, kinetics, experimental aspects, etc.) of electron exchange processes.